2022
DOI: 10.1093/ejcts/ezac208
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of patients undergoing re-exploration for bleeding following cardiac surgery: a SWEDEHEART study

Abstract: OBJECTIVES Excessive bleeding leading to re-exploration is a severe complication of cardiac surgical procedures, associated with early postoperative morbidity and mortality. Less is known about the long-term outcome of these patients. We evaluated the impact of re-exploration after cardiac surgery on peri- and postoperative morbidity and mortality, as well long-term mortality, in a well-defined nationwide population. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In our study, the mean age of patients was 62.7±5.6 years. This matches what was reported by Heimisdottir et al, who retrospectively reviewed more than 48,000 patients undergoing cardiac surgeries, either CABG or valve replacement, in the period between 2006 and 2015 [Heimisdottir 2022].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, the mean age of patients was 62.7±5.6 years. This matches what was reported by Heimisdottir et al, who retrospectively reviewed more than 48,000 patients undergoing cardiac surgeries, either CABG or valve replacement, in the period between 2006 and 2015 [Heimisdottir 2022].…”
Section: Discussionsupporting
confidence: 88%
“…They also performed a Cox regression analysis to identify the associated risk factors for chest re-exploration. They reported that only 4.9% of patients needed re-exploration among included patients and that advanced age was significantly associated with an increased exploration rate among patients [Heimisdottir 2022].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-and intraoperative patient characteristics have been repeatedly shown to be worse in patients at risk for postoperative ROB after cardiac surgery. [39] These patients are signi cantly older, have higher rates of heart and renal failure, have higher EuroSCORE II and preoperative aPTT values, and have lower hemoglobin levels than patients who did not undergo ROB. [21] In addition, emergency surgery and prolonged aortic cross-clamp time are independent risk factors for ROB.…”
Section: Commentmentioning
confidence: 99%
“…[21] In addition, emergency surgery and prolonged aortic cross-clamp time are independent risk factors for ROB. [39] The kidney is the organ most affected in critically ill patients. Fluid overload as a consequence of perioperative liberal uid management may explain why the incidence of renal dysfunction was higher in patients undergoing ROB.…”
Section: Commentmentioning
confidence: 99%